Influence of the Mettur Irrigation and Hydroelectric Project on Agriculture and Agroindustries - Planning Commission (Planning Commission, 1956)
This pilot survey was sponsored by the Research Programmes Committee of the Planning Commission and was financed by a grant from it. It was undertaken in the year 1956-57. The completion of the survey and report took about nine months. The survey was concentrated in the Pattukottai Taluk, which comprised of dry lands prior to the implementation of the Project.
Research Programmes Committee Planning Commission
Research Programmes Committee Planning Commission